Prywatność pacjenta jako dobro osobiste. Nowe wyzwania w świetle regulacji RODO - Wrześniewska-Wal, Iwona; Janiszewska, Lidia (Studia Prawnoustrojowe, 2019)
The article discusses the issue of changes in the catalog of legal instruments, which can be used by a patient when a violation of the principles of processing his personal rights occurs, in the context of the application of the EU General Data Protection Regulation (GDPR). It draws attention to the extension of the catalog of available legal instruments in the feld of personal data protection and the presents of other mechanisms aimed at protecting the rights of patients, including the right to privacy. The authors express a belief that, especially the administrative mode can be widely used by patients in the initial period of application of the General Data Protection Regulation.